2022
DOI: 10.1186/s40643-022-00611-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of operating parameters for biogas production using two-phase bench-scale anaerobic digestion of slaughterhouse wastewater: Focus on methanogenic step

Abstract: The objective of the present study was an optimization of operating parameters and the performance of the methanogenesis reactor in phased anaerobic digestion (AD) of slaughterhouse wastewater at 37.5°C. Accordingly, the feedstock of the methanogenic reactor was effluent from the hydrolytic-acidogenic reactor operating at HRT of 3-days and OLR of 1789 mg/L. The methanogenesis phase was also investigated at different hydraulic retention time (HRT) values ranging from 12 to 3 days at 3-day intervals, and organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…Mulu and Ayenew [10], Ren et al [54], and Worku and Leta [1] reported the COD values of the slaughterhouse as 4752.66 ± 1156.27 mg/L and 6942.59 ± 152.98-7079.69 ± 226.89 mg/L, respectively. Furthermore, slaughterhouses and meat-processing facilities produce a huge volume of wastewater with organic matter measured as COD between 500 and 15,900 mg/L [52], TVFA between 435 and 1197 mg/L [55], and NH 4 + -N between 186 and 6407 mg/L [1,46]. This high concentration of organic matter necessitates a greater amount of oxygen to be oxidized into carbon dioxide and water, which may contribute to an increase in the COD and BOD of the receiving water body [56].…”
Section: Characteristics Of Feedstock (Organic Export Abattoir Wastew...mentioning
confidence: 99%
“…Mulu and Ayenew [10], Ren et al [54], and Worku and Leta [1] reported the COD values of the slaughterhouse as 4752.66 ± 1156.27 mg/L and 6942.59 ± 152.98-7079.69 ± 226.89 mg/L, respectively. Furthermore, slaughterhouses and meat-processing facilities produce a huge volume of wastewater with organic matter measured as COD between 500 and 15,900 mg/L [52], TVFA between 435 and 1197 mg/L [55], and NH 4 + -N between 186 and 6407 mg/L [1,46]. This high concentration of organic matter necessitates a greater amount of oxygen to be oxidized into carbon dioxide and water, which may contribute to an increase in the COD and BOD of the receiving water body [56].…”
Section: Characteristics Of Feedstock (Organic Export Abattoir Wastew...mentioning
confidence: 99%
“…In developing countries, more than ninety percent of the agro-processing industries discharge partially treated or untreated effluents recklessly into the environment. The effluents from the agro-processing industries as well as anaerobic digestion (AD) effluents are known for their high organic matter, nutrients, and other pollutants that are unsafe to the receiving water bodies or environment (Zemene Worku and Seyom Leta 2017 ; Ashekuzzaman et al 2019 ; Bustillo-Lecompte and Mehrvar 2015 ; Hailu et al 2020 ; Yirgu et al 2020 ; K. Praveen et al 2018 ; Leta et al 2003 ), directing post-treatment process requirement to minimize or remove organic matters as organic and inorganic forms of phosphorus and nitrogen of the effluents (De Nardi et al 2011 ; Chevalier et al 2000 ; Dawana and Kassa 2020 ; Tsegaye and Leta 2022 ). If directly released, it results in eutrophication of the receiving water bodies and other environmental risks associated with greenhouse gas emissions from ammonia volatilization, groundwater nitrogen contamination, or pollution, and also affects human health via the food chain (Akar and Tunali 2005 ; Carey and Migliaccio 2009 ; Fornarelli, Bahri, and Moheimani 2017 ).…”
Section: Introductionmentioning
confidence: 99%